Jurisprudential analysis of the production and use of weapons of mass destruction - Hamed Rostami Najafabadi (مطالعات فقه و حقوق اسلامی)
Examining Islamic Jihad issues in resorting to military force and coercive actions against the enemy and the way to treat civilians and non-combatant people indicates that the humanitarian provisions of Islam are based on the fundamental principles that provide the necessary grounds for the implementation of Jihad rules in different conflict situations. They provide Islam. Justice, the right to life and respect for human dignity are among the foundations of humanitarian rights in Islam, each of which has a special place and importance in Jihad in the cause of Allah. Quranic evidence, narration, reason, consensus and Muslim jurisprudence rules have prohibited the production and use of weapons of mass destruction; Therefore, in this article, while examining the concept and examples of weapons of mass destruction, topics such as justice, the right to life, human dignity, which are discussed as the bases for not allowing the use of weapons of mass destruction, to examine the verses and traditions, reason and consensus, which are among the most important evidences for issuing verdicts. Regarding topics such as weapons of mass destruction; Paid. In this research, the prohibition of the production and use of weapons of mass destruction in Islamic jurisprudence has been analyzed, and in the books of the jurists of the previous examples, it can be revised and applied to the current examples; Also, the prohibition of using these weapons in normal conditions is based on customary rules.